VAGINAL MUCUS IMPEDANCE IN POSTPARTUM ANESTRUS MURRAH BUFFALOES TREATED WITH DIFFERENT HORMONAL REGIMEN - KALSOTRA, RAJAT; SHARMA, UTSAV; KUMAR, SUDHIR; KUMAR, SHARAD (The Indian Journal of Animal Reproduction, 2023)
Twenty four anestrus postpartum buffaloes were subjected to treatment with CIDR implant plus PGF2a, Hydroxyprogesterone plus PGF2a and Buseralin acetate in group I, II and Ill respectively. Estrus was exhibited by all the buffaloes in treatment group except in group IV which was kept as control. The mean Vaginal mucus impedance (VMI) in Group I, II and Ill were higher on the day of treatment and declined significantly (P<0.01) on the day of estrus. In responded animals the mean VMI were higher on the day of treatment (52.35±0.70 Ohms) and declined significantly (P<0.01) on the day of estrus (30.78±0.62 Ohms).